Combined Synchronization among Three Inconsistent Networks - Yuan Chai; Xiaojing Zhu; Jingjing Cai (Advances in Mathematical Physics)
A new type of network-combination synchronization is proposed between two drive networks, small-world and scale-free, and one response community network based on the model of multiple system combination. According to Lyapunov Stability Theorem, combined controllers are designed to control three disparate networks with different topological structures. A realistic combination model of multiple inhomogeneous networks and a universal controller are devised in the combination design. The paper is characterized by two parts of one response community network loaded from the combined signals of two drive networks. Numerical simulations are presented to show the full and partial control of the proposed method.